2016
DOI: 10.1016/j.scitotenv.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen content of the certain types of biodiesels on particulate oxidative potential

Abstract: Oxidative potential (OP) is related to the organic phase, specifically to its oxygenated organic fraction (OOA). Furthermore, the oxygen content of fuel molecules has significant influence on particulate OP. Thus, this study aimed to explore the actual dependency of the OOA and ROS to the oxygen content of the fuel. In order to reach the goal, different biodiesels blends, with various ranges of oxygen content; have been employed. The compact time of flight aerosol mass spectrometer (c-ToF AMS) enabled better i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 56 publications
2
29
1
Order By: Relevance
“…On the contrary, the correlation between BPEAnit and DTT is modest (r = 0.14), and again related to the sensitivity of these probes and the difference in the sampling approach. The correlation between DTT and BPEAnit found in this study is much lower than previously reported in the study by Hedayat et al [56], which can be attributed to the difference in the particle composition between real-world and laboratory-controlled emissions. In addition, Hedayat et al [56] measured fresh emissions directly coming from one source (a diesel vehicle), while in this study the emissions from a number of different vehicles, both petrol and diesel, were thoroughly mixed before sampling.…”
Section: Int J Environ Res Public Health 2019 16 X 11 Of 18contrasting
confidence: 95%
“…On the contrary, the correlation between BPEAnit and DTT is modest (r = 0.14), and again related to the sensitivity of these probes and the difference in the sampling approach. The correlation between DTT and BPEAnit found in this study is much lower than previously reported in the study by Hedayat et al [56], which can be attributed to the difference in the particle composition between real-world and laboratory-controlled emissions. In addition, Hedayat et al [56] measured fresh emissions directly coming from one source (a diesel vehicle), while in this study the emissions from a number of different vehicles, both petrol and diesel, were thoroughly mixed before sampling.…”
Section: Int J Environ Res Public Health 2019 16 X 11 Of 18contrasting
confidence: 95%
“…ROS content measured with the BPEAnit assay, which also determines PB-ROS, was in the range of 0.05 -0.4 nmol μg -1 for diesel/bio-diesel POA showing an increasing trend with the oxygen content of the fuel (Stevanovic et al, 2013;Hedayat et al, 2016). This assay also measured a higher PB-ROS content (0.2 -4 nmol μg -1 ) in primary aerosols from wood combustion (Miljevic et al, 2010).…”
Section: Comparison Of the Ros Content Of Oa From Different Sourcesmentioning
confidence: 95%
“…For instance, the 2′-7′-55 dichlorofluorescin (DCFH) and the p-hydroxyphenylacetic acid (POHPAA) assay respond to a range of organic peroxides (Venkatachari and Hopke, 2008;Wang et al, 2011a;King and Weber, 2013;Fuller et al, 2014;Zhou et al, 2018a;Hasson and Paulson, 2003) and are used to measure particle-bound ROS (PB-ROS). Similarly, the assay with 9,10-bis (phenylethynyl) anthracene nitroxide (BPEA-nit) measures the amount of PB-ROS including radicals and metals such as Cu + and Fe 2+ , but not the ROS generated from Fenton chemistry (Miljevic et al, 2010;Hedayat et al, 2016). On 60 the other hand, the dithiothreitol (DTT) assay is strongly sensitive to redox active components, i.e., transition metals and quinones and is considered as a good estimator of ROS generation in lung cells (Cho et al, 2005;Verma et al, 2012;Charrier and Anastasio, 2012;Fang et al, 2016;Weber et al, 2018), but is also sensitive to organic peroxides .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of triacetin as an additive for diesel and biodiesel also reduces the emission of pollutant. Regarding the investigations carried out on the blends triacetin/biodiesel and triacetin/diesel, the combination of 10% by weight of triacetin with biodiesel is the one that shows the best results [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170]. Finally, beneficial effects of triacetin on the cloud point and cold filter plugging point have also been revealed in several studies [171][172][173].…”
Section: Biodiesel-like Biofuels That Integrate Glycerol As Glycerol mentioning
confidence: 99%